2022
DOI: 10.1111/myc.13498
|View full text |Cite
|
Sign up to set email alerts
|

Deep convolutional neural networks for onychomycosis detection using microscopic images with KOH examination

Abstract: Background The diagnosis of superficial fungal infections is still mostly based on direct microscopic examination with potassium hydroxide solution. However, this method can be time consuming, and its diagnostic accuracy rates vary widely depending on the clinician's experience. Objectives This study presents a deep neural network structure that enables the rapid solutions for these problems and can perform automatic fungi detection in grayscale images without dyes. Methods One hundred sixty microscopic full f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The differences in diagnosing onychomycosis using CNN vs. manual microscopic examinations have been compared and analyzed. Results from one report found that the accuracy of CNN diagnosis was 10% greater than that of traditional diagnostic methods ( Yilmaz et al, 2022 ). In that study, 60 nail samples from patients with onychomycosis and 297 nail samples from healthy controls were treated with KOH.…”
Section: Recognition Of Fungi With Convolutional Neural Networkmentioning
confidence: 99%
“…The differences in diagnosing onychomycosis using CNN vs. manual microscopic examinations have been compared and analyzed. Results from one report found that the accuracy of CNN diagnosis was 10% greater than that of traditional diagnostic methods ( Yilmaz et al, 2022 ). In that study, 60 nail samples from patients with onychomycosis and 297 nail samples from healthy controls were treated with KOH.…”
Section: Recognition Of Fungi With Convolutional Neural Networkmentioning
confidence: 99%
“…It was found that the CNN had an AUC of 1.00 (99.84% accuracy). 18 In comparison, the average AUC value of clinicians is 0.87 (72.8% accuracy, determined through a meta-analysis of 11 studies 18 ). These results indicate that AI can accurately perform an automatic diagnosis of onychomycosis using fungi detection from grayscale microscopic images, and at a level that outperforms clinicians.…”
Section: Ai For Onychomycos Ismentioning
confidence: 99%
“…Yilmaz et al (2021) used a CNN to examine grayscale microscopic images of nail samples (as colorants can be expensive and time consuming) and determine diagnoses of onychomycosis. Microscopic images of fungi and keratin were taken from patients with distal and lateral onychomycosis 18. The samples were kept in 20% KOH for 15-20 min and then examined directly under a microscope by two experienced dermatologists and determined to be positive or not.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, deep learning systems that will work as a decision support mechanism for the diagnosis of skin diseases have begun to be developed for people such as inexperienced dermatologists, nurses, and primary care doctors who are not experts in the field of dermatology [ 22 , 23 ]. Teledermoscopy was studied based on feature extraction with a small binary dataset [ 24 ].…”
Section: Introductionmentioning
confidence: 99%